Association and dissociation kinetics of anti-hen egg lysozyme monoclonal antibodies HyHEL-5 and HyHEL-10. - Xavier, K A (1998)
The immunoglobulin G1 (IgG1) kappa antibodies HyHEL-5 and HyHEL-10 interact with nonoverlapping epitopes on hen egg lysozyme (HEL); the HyHEL-5/HEL interface has two energetically and structurally important salt links, whereas the HyHEL-10/HEL interface involves predominantly hydrogen bonds and van der Waals interactions. The kinetics of association and dissociation of antibodies HyHEL-5 and HyHEL-10 with HEL under a variety of conditions were investigated in this study. The association of each antibody with HEL follows second-order kinetics. The association process is significantly diffusion-limited, as indicated by the viscosity dependence of the interaction of both antibodies with HEL, although detailed energetics suggest that the association process may be more complex. The association rate constant for the HyHEL-5/HEL system is within a factor of 2 of the modified Smoluchowski estimate for proteins of this size, whereas HyHEL-10 interacts with HEL with an association rate an order of magnitude lower. The association reactions are insensitive to ionic strength, showing only a twofold decrease in the association rate constant when the ionic strength was increased from 27 mM to 500 mM. Interestingly, the association rate constant for the interaction of HyHEL-5 with HEL varies with pH in the range 6.0-10.0, whereas HyHEL-10/HEL association is not affected by pH in the same range. The dissociation of the HyHEL-5/HEL and HyHEL-10/HEL complexes follow first-order kinetics with half-lives at 25 degrees C of approximately 3,150 s and approximately 21,660 s, respectively.